Empathy and Prosocial Behavior Correlation Among Indonesian Junior High Students: Korelasi Antara Empati dan Perilaku Prosocial di Kalangan Siswa SMP Indonesia - Safira Abadi; Nurfi Laili (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Adolescence is a critical developmental period marked by rapid social and emotional changes, during which prosocial behavior plays a central role in fostering harmonious interpersonal relationships and school climate. Specific Background: Prosocial tendencies among adolescents have shown signs of decline alongside increasing individualistic orientations, highlighting the importance of internal psychological factors such as empathy in guiding helping, sharing, cooperating, donating, and honesty. Knowledge Gap: Although previous studies report a positive association between empathy and prosocial conduct, limited empirical evidence exists within Islamic-based junior high school settings in Indonesia, particularly at SMP Muhammadiyah 1 Sidoarjo. Aims: This study examined the relationship between empathy and prosocial behavior among adolescents in this educational context. Results: Using a quantitative correlational design with stratified sampling of 221 students in grades VII–IX and Pearson correlation analysis, the findings revealed a positive and statistically significant association between empathy and prosocial behavior (r = 0.528; p < 0.05), indicating a moderate relationship in which higher empathy levels correspond with greater participation in helping-oriented actions. Novelty: The research provides context-specific evidence from an Islamic-based school environment, contributing localized insight into adolescent social development within formal education. Implications: Empathy can be considered a key psychological component—though not the sole determinant—supporting prosocial engagement, suggesting that character education programs should incorporate empathy development to foster cooperative and caring student interactions. Highlights: A moderate positive statistical association was identified between empathy and helping-oriented actions among students. Participants with higher empathic disposition reported more frequent cooperation, sharing, and assistance toward others. Emotional understanding alone did not fully account for behavioral outcomes, indicating additional contributing factors. Keywords: Empathy; Prosocial Behavior; Adolescents; Junior High School students; Correlational Study